The Uncertainty Channel of Contagion - Kannan, Prakash (IMF Working Papers; Working Paper ;, 2009)
The 2007 subprime crisis in the U.S. triggered a succession of financial crises around the globe, reigniting interest in the contagion phenomenon. Not all crises, however, are contagious. This paper models a new channel of contagion where the degree of anticipation of crises, through its impact on investor uncertainty, determines the occurrence of contagion. Incidences of surprise crises lead investors to doubt the accuracy of their informationgathering technology, which endogenously increases the probability of crises elsewhere. Anticipated crisis, instead, have the opposite effect. Importantly, this channel is empirically shown to have an independent effect beyond other contagion channels.